Estratégias familiares e sustentabilidade econômica em assentamento rural - Gaspari, Luciane Cristina de (Universidade Federal de São Carlos, 2010)
The economic sustainability of family farms is a major factor in promoting sustainable development in areas of rural settlements. Thus, this study sought to identify systemic approach through what are the strategies of the families who work together for the perpetuation of the familiar form of land use in order to encourage them through public policies. As economic indicators we used the value-added and value added per worker, considering the relevant aspects of establishments such as family characteristics, socioeconomic, cultural and quality of life, work organization and production, productive infrastructure, level dependence, reproductive strategies and future expectations, and the commercialization of products. Among the strategies studied the agricultural income of family farms that sell to the agricultural industry has the best performance, however the dependency and risk are high, which can lead to economic sustainability. Already in establishments that do not trade with agro farm income is lower, but is more likely to persist over time. Among these establishments, farm products that drains directly is more advantageous from the perspective of agricultural income and consumption. This reaffirms the idea that the creation of sites for the direct marketing cooperation for sustainable development in the field with decent living conditions.
Family strategies and economic sustainability in rural settlement
Keywords: Agroecologia; Estratégia; Família; Sustentabilidade; Assentamento rural; Eestabelecimentos agrícolas familiares; Rentabilidade econômica; Family farms; Strategies; Profitability; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::CONSTRUCOES RURAIS E AMBIENCIA::ASSENTAMENTO RURAL